Medical Treatment for Acromegaly does not Increase the Risk of Central Adrenal Insufficiency: A Long-Term Follow-Up Study - Ceccato, F.; Lizzul, L.; Zilio, M.; Barbot, M.; Denaro, L.; Emanuelli, E.; Alessio, L.; Rolma, G.; Manara, R.; Saller, A.; Boscaro, M.; Scaroni, C. (Hormone and Metabolic Research, 2016)
Central adrenal insufficiency (CAI) in acromegaly may be related to pituitary adenoma or induced by various medical treatments, transsphenoidal neurosurgery (TNS) or radiotherapy (RT), alone or combined. We assessed the role of all available treatments for acromegaly in inducing CAI. We retrospectively studied 97 patients. CAI was diagnosed if morning serum cortisol was <138 nmol/l, or if its response was inadequate in the low-dose short synacthen test. Seventy-four subjects underwent TNS (and 17 of whom also underwent RT), and 23 were on primary medical therapy: overall we diagnosed 21 cases of CAI. Duration of acromegaly, invasion of cavernous sinus, disease control, and type of medical treatment were much the same for patients with and without CAI, which was identified in 18% of patients (10/57) after one TNS, and in 53% (9/17) after RT (p=0.01); repeat surgery increased the risk of CAI (p=0.02). The risk of CAI onset during the follow-up was lower among patients treated with TNS or medical therapy than after RT (p=0.035). Medical treatment did not raise the risk of CAI, whereas a 5- and 4-fold higher risk of CAI was associated with repeat TNS and RT, respectively. Basal or stimulated cortisol levels were similar among acromegalic patients without CAI and matched controls with nonsecreting pituitary lesions. A significant proportion of patients with acromegaly developed CAI over time. While primary or secondary medical treatment did not contribute to the risk of CAI, repeat TNS and RT correlated with pituitary-adrenal axis impairment.
Keywords: acromegaly; hypopituitarism; central adrenal insufficiency; radiotherapy; neurosurgery